Perovskite solar cell and preparation method thereof

By introducing small-molecular interface passivating agents such as thiolethylamine, ethylenediamine and propylamine into perovskite solar cells, the passivation layer is formed, which solves the problems of low photoelectric conversion efficiency and poor stability in perovskite solar cells, and improves the photoelectric conversion efficiency and enhances the stability.

CN119562693APending Publication Date: 2025-03-04SUZHOU VOCATIONAL UNIVERSITY (SUZHOU OPEN UNIVERSITY)
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411661684.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Perovskite solar cells have problems with low photoelectric conversion efficiency and poor stability, mainly due to poor uniformity of the perovskite layer, high defect state density, and poor interface contact between the perovskite layer and the hole transport layer.

Method used

Small-molecular interface passivators such as mercaptoethylamine (MEA), ethylenediamine (EDA) and propylamine (PA) are used to form a passivation layer of 1nm-10nm thick to improve the interface contact between the hole transport layer and the perovskite layer in perovskite solar cells, and optimize the component uniformity and defect state distribution of the perovskite layer.

Benefits of technology

By introducing small molecule interface passivator, the photoelectric conversion efficiency of perovskite solar cells is significantly improved, reaching 22.05%, and the stability and environmental stability of the device are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119562693A_ABST
    Figure CN119562693A_ABST
Patent Text Reader

Abstract

The invention relates to a perovskite solar cell and a preparation method thereof, and belongs to the technical field of solar cells. The perovskite solar cell comprises a conductive substrate, a hole transport layer, a passivation layer, a perovskite layer, an electron transport layer and a metal electrode which are arranged in sequence, the material of the passivation layer is selected from one or more of mercaptoethylamine, ethylenediamine and propylamine; and the thickness of the passivation layer is 1 nm to 10 nm. Through the introduction of interface passivator molecules, the interface between the hole transport layer and the perovskite layer is improved. The surface wettability of the PTAA thin film is enhanced, so that the perovskite precursor solution can form a uniform and compact perovskite layer on the PTAA / SCAs thin film, the carrier separation and transmission efficiency at an interface is improved, and the stability of a device is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solar cells, and in particular relates to a perovskite solar cell and a preparation method thereof. Background Art

[0002] With the continuous growth of global energy demand and the increasing emphasis on clean energy, the development and utilization of solar energy as a sustainable and pollution-free energy form has attracted much attention. Perovskite solar cells have become a research hotspot in the field of solar cells due to their high photoelectric conversion efficiency, low cost and easy preparation.

[0003] However, perovskite solar cells still face some challenges. For example, although CsFA-based perovskite solar cells have the advantages of high device photoelectric conversion efficiency, good operation stability, low material cost, and good film flexibility, their photoelectric conversion efficiency still needs to be improved compared with FA-based devices. This is mainly due to the fact that FA + and Cs + The mismatch in ion sizes and their different crystal dynamics lead to poor composition uniformity and high defect state density in the CsFAPbI3 perovskite layer. In addition, the surface defects generated in the hole transport layer of inverse perovskite solar cells also have a significant impact on the photoelectric conversion efficiency and operational stability of the device.

[0004] Poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine) (PTAA) is a widely used hole transport material in trans-structured perovskite solar cells. Its excellent hole mobility and proper energy level matching help improve cell performance. However, the high hydrophobicity of PTAA will adversely affect the interface contact between the perovskite layer and PTAA, limiting the carrier transport efficiency in the device. Its application in perovskite solar cells mainly has the following three forms:

[0005] First, in traditional perovskite solar cells, hole transport layer materials such as PTAA are directly spin-coated on the electron transport layer. However, due to the lack of optimization of the interface between the perovskite layer and the hole transport layer, and the presence of FA in the perovskite material itself, + and Cs +Problems such as ion size mismatch and different crystal dynamics result in poor component uniformity of the perovskite layer, high defect state density, many defect states inside the battery, and serious carrier recombination, which greatly limits the improvement of photoelectric conversion efficiency. For example, the photoelectric conversion efficiency of traditional CsFAPbI3-based perovskite solar cells can only reach about 15%-18%. In addition, due to the poor interface contact between the perovskite layer and the hole transport layer, charge recombination centers are easily generated at the interface, affecting the stability of the battery. Battery performance is prone to attenuation during long-term use or environmental changes. For example, in a high temperature and high humidity environment, the photoelectric conversion efficiency of the battery may drop significantly in a short period of time.

[0006] Second, in the unoptimized hole transport layer perovskite solar cells, hole transport layer materials such as PTAA are dissolved in solvents such as chlorobenzene, prepared into a solution of a certain concentration, and then spin-coated on the electron transport layer. However, due to the high hydrophobicity of PTAA, the interface affinity between it and the perovskite layer is low, the interface contact is poor, and there is a large obstacle to the transmission of carriers at the interface, which affects the filling factor of the battery and the overall photoelectric conversion efficiency. For example, the filling factor of the unoptimized hole transport layer perovskite solar cell is only about 70%-75%. In addition, since the molecular structure and performance of PTAA itself have not been improved, its hole mobility and conductivity have not been effectively improved, and the role of the hole transport layer cannot be fully utilized, resulting in the battery's filling factor and open circuit voltage being limited, making it difficult to achieve efficient charge collection and transmission.

[0007] Third, in perovskite solar cells with single-function additives, some single-function additives are added, such as using only certain substances to improve the crystallinity of the perovskite layer, or simply chemically modifying the surface of the perovskite to reduce defects. However, single-function additives can only improve battery performance in one aspect, and cannot comprehensively solve the various problems faced by perovskite solar cells, such as crystallization quality, interface characteristics, energy level matching, etc. For example, some functional additives can improve the crystallinity of perovskite to a certain extent, but have poor inhibitory effects on charge recombination at the interface, or cannot effectively improve the performance of the hole transport layer, resulting in limited overall performance improvements in the battery, such as photoelectric conversion efficiency and stability. In addition, due to the interrelationships between various factors, it is difficult for single-function additives to achieve synergy between various factors. For example, in the process of improving the crystallization of perovskite, the original interface balance may be destroyed, or the optimization of crystallization and interface contact may not be taken into account when adjusting the energy level, thereby failing to fully realize the performance potential of the battery.

[0008] Therefore, it is still of great significance to develop a method that can effectively improve the overall performance of perovskite solar cells. Summary of the invention

[0009] Therefore, the technical problem to be solved by the present invention is to overcome the problems of low photoelectric conversion efficiency and poor stability of perovskite solar cells in the prior art.

[0010] In order to solve the above technical problems, the present invention provides a perovskite solar cell and a preparation method thereof.

[0011] The first object of the present invention is to provide a perovskite solar cell, comprising a conductive substrate, a hole transport layer, a passivation layer, a perovskite layer, an electron transport layer and a metal electrode arranged in sequence;

[0012] The material of the passivation layer is selected from one or more of mercaptoethylamine (MEA), ethylenediamine (EDA) and propylamine (PA); the thickness of the passivation layer is 1nm-10nm.

[0013] In one embodiment of the present invention, mercaptoethylamine (MEA), ethylenediamine (EDA) and propylamine (PA) are used as interface passivators in perovskite solar cells, including the formation of a passivation layer on the surface of a hole transport layer and the addition method and concentration range during the treatment of a perovskite precursor solution.

[0014] In one embodiment of the present invention, the conductive substrate is selected from fluorine tin oxide transparent conductive glass (FTO) and / or indium tin oxide transparent conductive glass (ITO).

[0015] In one embodiment of the present invention, the material of the hole transport layer is poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine) (PTAA); the thickness of the hole transport layer is 50nm-150nm.

[0016] In one embodiment of the present invention, the material of the perovskite layer is ABX3 type perovskite, wherein the A position is selected from the group consisting of formamidinium cation (HC(NH2)2 + , F.A. + ) and / or methylamine cation (CH3NH3 + , M.A. + ); X is selected from fluoride ion (F - ), chloride ion (Cl - ), bromide ion (Br - ) and iodide ion (I - );The thickness of the perovskite layer is 500nm-600nm.

[0017] In one embodiment of the present invention, the material of the electron transport layer is selected from PC 61 BM and / or C 60 ; The thickness of the electron transport layer is 20nm-100nm.

[0018] In one embodiment of the present invention, the metal electrode is selected from one or more of gold, silver, copper and indium tin oxide; the thickness of the metal electrode is 80nm-300nm.

[0019] The second object of the present invention is to provide a method for preparing the perovskite solar cell, comprising the following steps:

[0020] S1, coating the mixed solution on the surface of the conductive substrate to form a hole transport layer; the mixed solution is obtained by dissolving the material of the hole transport layer in the first solvent;

[0021] S2, applying a passivating agent solution on the surface of the hole transport layer to form a passivating layer; the passivating agent solution is obtained by dissolving a passivating agent in a second solvent;

[0022] S3, sequentially preparing a perovskite layer, an electron transport layer and a metal cathode electrode on the surface of the hole transport layer to obtain the perovskite solar cell.

[0023] In one embodiment of the present invention, in S1, the concentration of the mixed solution is 2 mg / mL-10 mg / mL.

[0024] In one embodiment of the present invention, in S2, the concentration of the passivating agent solution is 1 mg / mL-5 mg / mL.

[0025] In one embodiment of the present invention, the first solvent is selected from chlorobenzene and / or toluene; the second solvent is selected from one or more of N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO) and isopropyl alcohol (IPA).

[0026] The technical solution of the present invention has the following advantages over the prior art:

[0027] (1) The perovskite solar cell of the present invention improves the interface between the hole transport layer and the perovskite layer by introducing interface passivating agent (SCAs) molecules. The SCAs small molecules enhance the wettability of the surface of the PTAA film, allowing the perovskite precursor solution to form a uniform and dense perovskite layer on the PTAA / SCAs film, thereby improving the carrier separation and transmission efficiency at the interface.

[0028] (2) The nitrogen (N), sulfur (S) and other heteroatoms contained in the small molecule interface passivator molecules used in the perovskite solar cell of the present invention can react with the lead (Pb) in the perovskite layer. 2+ ) ions form coordination bonds, effectively passivating Pb 2+ As well as Pb-I related defects, non-radiative recombination at the interface is reduced, thereby improving the photoelectric conversion efficiency of perovskite solar cells, and the photoelectric conversion efficiency of perovskite solar cells reaches 22.05%.

[0029] (3) The small molecule interface passivator used in the perovskite solar cell described in the present invention can optimize the flatness of the hole transport layer, fill the hole defects on the surface of the hole transport layer, provide a good foundation for the subsequent growth of the perovskite layer, make the surface of the perovskite layer more uniform and dense, reduce grain boundaries and surface defects, thereby improving the quality of the perovskite layer and enhancing the stability of the device.

[0030] (4) The perovskite solar cell described in the present invention enhances the hydrophobicity of the surface of the perovskite layer by introducing small molecule interface passivators (SCAs), which can block the penetration of water molecules, inhibit the degradation of the perovskite layer in a humid environment, and improve the environmental stability of the device.

[0031] (5) The perovskite solar cell described in the present invention improves the ion mobility and conductivity of the PTAA film by adding small molecule interface passivator molecules, optimizes the molecular structure and orientation of PTAA, thereby improving its charge transfer performance, facilitating the hole extraction and transfer process at the interface, and further improving the photovoltaic performance of the device.

[0032] (6) The HOMO and Fermi levels of the PTAA film modified with a small molecule interface passivator in the perovskite solar cell described in the present invention both move toward the vacuum energy level, thereby making the energy level match between the PTAA film and the perovskite layer better, promoting hole transport at the interface, and reducing charge recombination. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:

[0034] Figure 1 This is a JV hysteresis curve diagram of the perovskite solar cell of Test Example 1 of the present invention;

[0035] Figure 2 This is a steady-state output current diagram of the perovskite solar cell of Test Example 2 of the present invention;

[0036] Figure 3 This is a statistical diagram of performance parameters of the perovskite solar cell of Test Example 3 of the present invention;

[0037] Figure 4 The contact angle diagrams of the perovskite precursor solution of Test Example 4 of the present invention on the PTAA film and the PTAA / SCAs film; wherein (a) is Comparative Example 1, (b) is Example 1, (c) is Example 2, and (d) is Example 3;

[0038] Figure 5AFM images of the PTAA film and PTAA / SCAs film of Test Example 5 of the present invention;

[0039] Figure 6 The optical properties and photovoltaic performance of the PTAA film and PTAA / SCAs film of Test Example 6 of the present invention;

[0040] Figure 7 The water contact angle diagram of the perovskite layer of Test Example 7 of the present invention; wherein (a) is Comparative Example 1, (b) is Example 1, (c) is Example 2, and (d) is Example 3;

[0041] Figure 8 This is an AFM image of the perovskite layer of Test Example 8 of the present invention;

[0042] Fig. 9 The SEM image and grain distribution diagram of the perovskite layer of Test Example 9 of the present invention

[0043] Fig.10 The steady-state PL spectrum (a) and TRPL decay curve (b) of the perovskite layer of Test Example 10 of the present invention;

[0044] Fig.11 4fXPS spectrum of Pb of the perovskite layer of Test Example 11 of the present invention;

[0045] Fig.12 3dXPS spectrum of the perovskite layer of Test Example 11 of the present invention;

[0046] Fig.13 The thermal stability test (a) and storage stability test (b) of the perovskite solar cell of Test Example 12 of the present invention;

[0047] Fig.14 This is the continuous illumination stability test of the perovskite solar energy of Test Example 13 of the present invention. DETAILED DESCRIPTION

[0048] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0049] In the present invention, unless otherwise explained, technical and scientific terms used in the present invention have the same meanings as commonly understood by those skilled in the art to which the present invention belongs.

[0050] In the present invention, unless otherwise stated, the term "and / or" used in the present invention includes any and all combinations of one or more of the associated listed items.

[0051] In the present invention, unless otherwise stated, the experimental methods used in the embodiments of the present invention are conventional methods unless otherwise stated, and the materials, reagents, etc. used are all commercially available unless otherwise stated.

[0052] Example 1

[0053] The perovskite solar cell and the preparation method thereof of the present embodiment specifically include the following steps:

[0054] S1. Pretreatment of the conductive substrate: A 2.5 cm×2.5 cm indium tin oxide transparent conductive glass (ITO) was ultrasonically cleaned for 30 min using a glass cleaning agent, deionized water, and alcohol, respectively, and then dried using a nitrogen gun, and then subjected to ultraviolet ozone treatment to obtain a pretreated conductive substrate;

[0055] S2. Preparation of hole transport layer: poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine) (PTAA) was dissolved in chlorobenzene to prepare a PTAA solution with a concentration of 3 mg / mL, and then the PTAA solution was spin-coated on the pretreated conductive substrate by spin coating at a speed of 5500 rpm for 30 s. After natural drying, a hole transport layer with a thickness of about 100 nm was formed;

[0056] S3, preparation of passivation layer: dissolving mercaptoethylamine (MEA) in N,N-dimethylformamide (DMF) to prepare a MEA solution with a concentration of 2 mg / mL, and then spin-coating the MEA solution on the hole transport layer at a spin-coating speed of 5000 rpm for 30 seconds to form a passivation layer with a thickness of about 10 nm;

[0057] S4. Preparation of perovskite layer: PbI2 and FAI were dissolved in a mixed solution of N,N-dimethylformyl (DMF) (800 μL) and N,N-dimethylformyl (DMSO) (50 μL) at a molar ratio of 100:85, and then 150 μL of CsI solution (DMSO solution with a CsI concentration of 1.4 mol / L) was added to obtain a perovskite precursor solution; the perovskite precursor solution was spin-coated on the passivation layer, and the program was set to two stages, the spin-coating speed of the first stage was 1000 rpm, the spin-coating time was 5 s, and the acceleration was 500 rpm / s, and the spin-coating speed of the second stage was 4000 rpm, the spin-coating time was 30 s, and the acceleration was 2000 rpm / s; when the spin-coating was to the last 10 s, 150 μL of chlorobenzene was used as an anti-solvent for washing, and then annealed at 100°C for 10 min, and naturally cooled to room temperature to form a perovskite layer with a thickness of about 600 nm;

[0058] S5. Preparation of electron transport layer: weigh 10 mg PC 61 BM and 10 mg C 60After mixing, dissolve in o-dichlorobenzene to prepare a PC solution with a concentration of 20 mg / mL. 61 BM:C 60 The solution was dropped onto the perovskite layer, and the program was set to two stages. The first stage had a spin coating speed of 1000 rpm, a spin coating time of 60 s, and an acceleration of 500 rpm / s; the second stage had a spin coating speed of 4000 rpm, a spin coating time of 10 s, and an acceleration of 2000 rpm / s, forming an electron transport layer with a thickness of about 50 nm.

[0059] S6. Preparation of metal electrode: Prepare a gold electrode with a thickness of about 100 nm on the perovskite layer.

[0060] Example 2

[0061] The method is basically the same as Example 1, except that the passivation layer is prepared by replacing mercaptoethylamine (MEA) with ethylenediamine (EDA).

[0062] Example 3

[0063] The method is basically the same as Example 1, except that the passivation layer is prepared by replacing mercaptoethylamine (MEA) with propylamine (PA).

[0064] Comparative Example 1

[0065] The method is basically the same as the first embodiment, except that no passivation layer is provided.

[0066] Test Example 1

[0067] Under standard illumination conditions, the JV characteristic curves of the perovskite solar cells of Examples 1-3 and Comparative Example 1 were compared, and the results are as follows: Figure 1 As shown. Figure 1 It can be seen that compared with Comparative Example 1, the JV curve shape of the perovskite solar cell of the embodiment is significantly optimized, and the photoelectric conversion efficiency is significantly improved.

[0068] Test Example 2

[0069] The stable output power of the perovskite solar cells of Examples 1-3 and Comparative Example 1 at the maximum power point (MPP) was tested, and the results were as follows: Figure 2 As shown. Figure 2 It can be seen that the perovskite solar cell of the embodiment shows a more stable output efficiency under the MPP condition. Compared with Comparative Example 1, the perovskite solar cell of the embodiment shows a higher open circuit voltage and steady-state output current density at MPP, which indicates that the introduction of SCAs small molecules optimizes the overall performance of the perovskite solar cell.

[0070] Test Example 3

[0071] The statistical results of the photoelectric parameters of the perovskite solar cells of Examples 1-3 and Comparative Example 1 are as follows: Figure 3 As shown. Figure 3 It can be seen that compared with Comparative Example 1, the photoelectric conversion efficiency of the perovskite solar cell of the embodiment is significantly improved. The photoelectric conversion efficiency of the perovskite solar cell of Comparative Example 1 is concentrated at about 19%, with a certain degree of discreteness; after the introduction of SCAs small molecules such as MEA, EDA or PA, the photoelectric conversion efficiency of the perovskite solar cell is significantly increased to 21%-22.1%, and the distribution is more concentrated. Among them, the photoelectric conversion efficiency of the MEA-optimized perovskite solar cell is the highest, reaching 22.05%, and shows good repeatability.

[0072] Test Example 4

[0073] Based on Examples 1-3 and Comparative Example 1, the contact angle test results of the perovskite precursor solution on the PTAA film and the PTAA / SCAs film are as follows: Figure 4 As shown. Figure 4 It can be seen that compared with the PTAA film of Comparative Example 1, the perovskite precursor solution shows a significantly smaller contact angle on the PTAA / SCAs film, indicating that the presence of SCAs small molecules can increase the affinity of the PTAA surface to the perovskite precursor solution. Further comparison of the PTAA / MEA film, the PTAA / EDA film and the PTAA / PA film shows that the contact angle of the perovskite precursor solution on the PTAA / MEA film and the PTAA / EDA film is smaller and the wettability is better. This is because the MEA molecule contains a hydrophilic thiol functional group. The wettability of the PTAA / EDA film is better than that of PTAA / PA, which is related to the fact that the EDA molecule has one more amino functional group than PA, which increases its affinity with the perovskite precursor solution. Good wettability is conducive to the formation of a uniform and dense perovskite layer of the perovskite precursor solution on the PTAA / SCAs film, improving the carrier separation and transmission efficiency at the interface.

[0074] Test Example 5

[0075] Based on Examples 1-3 and Comparative Example 1, the PTAA film and the PTAA / SCAs film were characterized. The AFM characterization results are as follows: Figure 5 As shown. Figure 5It can be seen that compared with the PTAA film of comparative example 1, after the SCAs small molecules are introduced into the PTAA film, the morphology of the film surface has changed significantly. The surface roughness value of the PTAA / SCAs film is lower than that of the PTAA film. The reduction in surface roughness indicates that the presence of SCAs makes the surface of the PTAA film smoother and denser. This is mainly because the SCAs small molecules can improve the film-forming quality of the PTAA film and fill the hole defects on the surface of the PTAA film, thereby optimizing the surface morphology. Generally speaking, a lower surface roughness is conducive to the growth of the subsequent perovskite layer. When the perovskite precursor solution is spin-coated on a flat and dense PTAA / SCAs film, a more uniform and dense perovskite grain growth can be obtained, and grain boundaries and surface defects can be reduced, thereby improving the quality of the perovskite layer.

[0076] Test Example 6

[0077] Based on Examples 1-3 and Comparative Example 1, the transmittance and bandgap (Eg) of the PTAA film and the PTAA / SCAs film were tested. The results are as follows: Figure 6 (a)- Figure 6 (b). Figure 6 (a)- Figure 6 (b) It can be seen that the introduction of SCAs small molecules has no significant effect on the basic optical properties of PTAA film, and its transmittance curve and band gap value are basically consistent with those of PTAA film, indicating that SCAs small molecules do not change the basic optical properties of PTAA.

[0078] Based on Examples 1-3 and Comparative Example 1, the mobility and conductivity of the PTAA film and the PTAA / SCAs film were tested. The results are as follows: Figure 6 (c)- Figure 6 (d). Figure 6 (c)- Figure 6 (d) It can be seen that the addition of SCAs small molecules improves the ion mobility and conductivity of the PTAA film. This is because the heteroatoms such as N and S contained in the SCAs small molecules can interact with PTAA, optimize the molecular structure and orientation of PTAA, and thus improve its charge transport performance. As the hole transport layer of perovskite solar cells, the charge transport performance of PTAA film directly affects the hole extraction and transport process at the interface, thereby affecting the photovoltaic performance of perovskite solar cells.

[0079] Test Example 7

[0080] Based on Examples 1-3 and Comparative Example 1, the water contact angle test results of the perovskite layer are as follows: Figure 7 As shown. Figure 7It can be seen that compared with the PTAA / perovskite layer of Comparative Example 1, the perovskite layer grown after the introduction of SCAs small molecules on the PTAA film obviously shows a larger water contact angle, which means that the film surface has a stronger hydrophobicity. This is because the SCAs small molecules have a certain hydrophobicity. When they exist at the PTAA / perovskite interface, they can change the chemical environment and surface energy of the perovskite layer surface, making it show a stronger hydrophobic property. Among them, the perovskite layer grown on the MEA substrate has the strongest hydrophobicity. The improvement of hydrophobicity is of great significance for optimizing the stability of the perovskite layer. The hydrophobic surface can block the penetration of water molecules, thereby inhibiting the degradation of the perovskite layer in a humid environment and improving the environmental stability of the perovskite solar cell.

[0081] Test Case 8

[0082] Based on Examples 1-3 and Comparative Example 1, the AFM characterization results of the perovskite layer are as follows Figure 8 As shown. Figure 8 It can be seen that when the perovskite layer grows on the PTAA / SCAs film, it shows a smoother and denser surface microstructure than the perovskite layer grown only on the PTAA film of Comparative Example 1. In particular, the root mean square roughness of the perovskite layer on the PTAA / MEA film is only 21.4nm, while it is 24.3nm on the PTAA film. This is because of the two effects of the MEA small molecules: First, the MEA molecules can improve the wettability of the PTAA surface to the perovskite precursor solution, promote the uniform and dense growth of the perovskite grains, and reduce grain boundaries and surface defects. Second, the MEA molecules themselves can also optimize the flatness of the PTAA film, laying a good foundation for the preparation of high-quality perovskite layers.

[0083] Test Example 9

[0084] Based on Examples 1-3 and Comparative Example 1, the top view of the perovskite layer and the grain distribution diagram are shown in FIG. Fig. 9 As shown. Fig. 9It can be seen that some bright spots appear in the perovskite layer grown on the PTAA film, and these bright spots are PbI2 residual phases. The presence of PbI2 residual phases indicates that the perovskite precursor is not completely converted on the PTAA surface, which will lead to an increase in defect states and affect the performance of perovskite solar cells. In the perovskite layer grown on the PTAA / SCAs film, this bright spot is significantly reduced, indicating that the crystallization of the perovskite is more complete. At the same time, the grain size distribution of the perovskite layer of the embodiment is also more uniform, because the SCAs small molecules can enhance the wettability of the PTAA film surface to the perovskite precursor solution, reduce the surface energy of the film, and thus improve the crystallization rate and uniformity of the perovskite. On the PTAA film of Comparative Example 1, the average grain size of the perovskite is about 191nm. The grain size of the perovskite grown on the PTAA / MEA, PTAA / EDA and PTAA / PA passivation layers is significantly increased, which are 225nm, 219nm and 230nm, respectively. Combining the characterization results of AFM and SEM, it can be seen that SCAs small molecules can improve the surface properties of PTAA films, provide a smoother and more hydrophobic growth environment, and thus optimize the morphology and crystallization quality of the perovskite layer.

[0085] Test Example 10

[0086] Based on Examples 1-3 and Comparative Example 1, the effects of SCAs on the charge recombination and transfer properties in the perovskite layer can be evaluated by photoluminescence (PL) and time-resolved (TRPL) spectroscopy. The results are as follows: Fig.10 As shown. Fig.10 (a) It can be seen that, whether measured from the surface of the perovskite layer (Top) or the conductive substrate (Bottom), the PL emission peak position of all samples is located at about 800nm, which is consistent with the typical band gap value of the perovskite material. When measured from the surface of the perovskite layer, the luminescence peak of the perovskite layer prepared on the PTAA / SCAs film all showed a lower PL intensity. This means that the SCAs small molecules can promote charge transfer and extraction within the perovskite layer. When measured from the conductive substrate, the PL intensity of the luminescence peak of the PTAA / MEA sample showed a more obvious PL quenching effect compared with the PTAA, PTAA / EDA and PTAA / PA samples. This shows that in the presence of MEA molecules, the hole transport and extraction efficiency between the perovskite layer and the PTAA film has been significantly improved. From Fig.10(b) It can be seen that the fast decay lifetime of the PTAA / perovskite layer in comparative example 1 is 12.56ns, accounting for 30.76%, while in the PTAA / MEA / perovskite sample, the fast decay lifetime is 6.67ns, accounting for 22.28%. This shows that the MEA small molecule optimizes the interface morphology and defect state distribution. The slow decay lifetime of the PTAA / perovskite layer in comparative example 1 is 354.17ns, accounting for 69.2%; the slow decay lifetime of the PTAA / MEA sample is 69.11ns, accounting for 77.72%. This is because MEA improves the crystallization quality and defect states of the perovskite layer. TRPL results show that the introduction of SCAs small molecules helps to achieve more efficient charge extraction and transport.

[0087] Test Example 11

[0088] The perovskite layers of Example 1 and Comparative Example 1 were deeply profiled by gas cluster ion sputtering (GCIS) technology, and the chemical composition and defect distribution inside the perovskite layer were analyzed by X-ray photoelectron spectroscopy (XPS). The X-ray photoelectron spectroscopy (XPS) of Pb 4f and I 3d of the perovskite layer on the PTAA film and PTAA / MEA film was collected at different sputtering times (0-500s). The results are as follows: Fig.11 and Fig.12 As shown, the longer the sputtering time, the deeper the corresponding detection depth.

[0089] from Fig.11 It can be seen that the Pb 2+ Pb 4f 5 / 2 and Pb 4f 7 / 2 The characteristic peaks are located at 142.8eV and 137.9eV respectively. 2+ Pb 4f 5 / 2 and Pb 4f 7 / 2 The characteristic peaks are located at 143.0eV and 138.1eV, respectively, and a chemical shift of about 0.3eV occurs in the direction of high binding energy, indicating that the presence of MEA small molecules changes the Pb 2+ As the etching time increases, Pb 0 4f 5 / 2 and Pb 0 4f 7 / 2 peak, indicating that there are uncoordinated Pb 0 defects. The closer to the PTAA / perovskite interface, the 0 The relative intensity of the peak gradually increased, while the Pb 2+ The peak gradually weakens. 0 With Pb2+ The results of quantitative analysis of the peak area are shown in Table 1:

[0090] Table 1

[0091]

[0092] It can be seen from Table 1 that the Pb 0 / Pb 2+ The ratio is significantly higher than that of PTAA / MEA / perovskite layer. This shows that the presence of MEA small molecules can effectively inhibit the Pb 0 The formation of defects improves the crystal quality of perovskite. 0 Defects are a common type of point defects in perovskite materials, which will form non-radiative recombination centers and accelerate the non-radiative energy decay of carriers. 0 The number of defects will inevitably suppress the non-radiative recombination losses of the perovskite layer, extend the carrier lifetime, and thus improve the open circuit voltage and other parameters of perovskite solar cells.

[0093] from Fig.12 It can be seen that the characteristic peak position of I3d of the perovskite layer prepared on the PTAA film or the PTAA / MEA film remains stable in the entire film thickness range without obvious chemical shift. 3 / 2 and I 3d 5 / 2 They are located at 630.2eV and 618.8eV respectively, which is consistent with I - The chemical valence values ​​of the two peaks are consistent. In the PTAA / MEA / perovskite layer, the positions of the two characteristic peaks slightly shift to high binding energy, and are located at 630.4eV and 618.9eV, respectively. This indicates that the introduction of MEA small molecules can optimize the morphology and defect state distribution of the perovskite / PTAA interface, and has a positive effect on the internal I - It is worth mentioning that for both PTAA and PTAA / MEA samples, the position of the I 3d peak on the surface of the perovskite layer undergoes a certain chemical shift relative to the interior of the film during 0s sputtering. This is due to the presence of certain defects on the perovskite surface or the surface I caused by ion migration. - The chemical environment has changed.

[0094] Test Example 12

[0095] The perovskite solar cells of 1-3 and comparative example 1 were placed in a high temperature environment of 85°C and tested for thermal stability under nitrogen protection. The results are as follows: Fig.13 (a). Fig.13(a) It can be seen that the photoelectric conversion efficiency of the perovskite solar cell of Comparative Example 1 drops to 91% of the initial value after 300 hours, while the photoelectric conversion efficiency of the perovskite solar cell of the embodiment only drops to about 95% of the initial value. This directly confirms that SCAs small molecules can significantly improve the thermal stability of perovskite cells.

[0096] The perovskite solar cells of 1-3 and comparative example 1 were placed in a glove box filled with nitrogen in the dark to test their storage stability. The results are as follows: Fig.13 (b). Fig.13 (b) It can be seen that the perovskite solar cells of Comparative Example 1 and the embodiment remain almost unchanged during the 1500h test period. This shows that the perovskite solar cell itself has good storage stability at room temperature and without exposure to air.

[0097] Test Example 13

[0098] At 100mW / cm 2 Under standard illumination conditions, the perovskite solar cells of Example 1 and Comparative Example 1 were tested for long-term operation stability at the maximum power point (0.94 V). The results are as follows Fig.14 As shown. Fig.14 It can be seen that after 300 hours of continuous illumination, the photoelectric conversion efficiency of the perovskite solar cell of Comparative Example 1 is only maintained at 88% of the initial value, while the photoelectric conversion efficiency of the perovskite solar cell of Example 1 can maintain 97% of the initial value. This result once again verifies that MEA small molecules can improve the long-term operation stability of perovskite cells.

[0099] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A perovskite solar cell, characterized in that: It includes a conductive substrate, a hole transport layer, a passivation layer, a perovskite layer, an electron transport layer and a metal electrode arranged in sequence; The material of the passivation layer is selected from one or more of mercaptoethylamine, ethylenediamine and propylamine; the thickness of the passivation layer is 1nm-10nm.

2. The perovskite solar cell according to claim 1, characterized in that The conductive substrate is selected from fluorine tin oxide transparent conductive glass and / or indium tin oxide transparent conductive glass.

3. The perovskite solar cell according to claim 1, characterized in that The material of the hole transport layer is poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine); the thickness of the hole transport layer is 50nm-150nm.

4. The perovskite solar cell according to claim 1, characterized in that: The material of the perovskite layer is ABX3 type perovskite, wherein the A position is selected from formamidinium cation and / or methylamine cation; the X position is selected from one or more of fluoride ion, chloride ion, bromide ion and iodide ion; the thickness of the perovskite layer is 500nm-600nm.

5. The perovskite solar cell according to claim 1, characterized in that: The material of the electron transport layer is selected from PC 61 BM and / or C 60 ; The thickness of the electron transport layer is 20nm-100nm.

6. The perovskite solar cell according to claim 1, characterized in that: The metal electrode is selected from one or more of gold, silver, copper and indium tin oxide; the thickness of the metal electrode is 80nm-300nm.

7. The method for preparing a perovskite solar cell according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, coating the mixed solution on the surface of the conductive substrate to form a hole transport layer; the mixed solution is obtained by dissolving the material of the hole transport layer in the first solvent; S2, applying a passivating agent solution on the surface of the hole transport layer to form a passivating layer; the passivating agent solution is obtained by dissolving a passivating agent in a second solvent; S3, sequentially preparing a perovskite layer, an electron transport layer and a metal cathode electrode on the surface of the hole transport layer to obtain the perovskite solar cell.

8. The method for preparing a perovskite solar cell according to claim 7, characterized in that: In S1, the concentration of the mixed solution is 2 mg / mL-10 mg / mL.

9. The method for preparing a perovskite solar cell according to claim 7, characterized in that: In S2, the concentration of the passivating agent solution is 1 mg / mL-5 mg / mL.

10. The method for preparing a perovskite solar cell according to claim 7, characterized in that: The first solvent is selected from chlorobenzene and / or toluene; the second solvent is selected from one or more of N,N-dimethylformamide, dimethyl sulfoxide and isopropanol.

Citation Information

Cited By

  • Solar cell based on single-layer two-dimensional-three-dimensional-two-dimensional gradient structure perovskite thin film

    CN114300620A

  • Method for gas-phase passivation of perovskite thin film by diamine and perovskite solar cell

    CN121099873A